Land grabbing and bioprospecting in the perspective of the right to own environmental resources - Krajewski, Piotr (Studia Iuridica Toruniensia, 2023)
The constant contact of man with nature prompted him to look for the best possible ways of using the earth and its biological resources. The accompanying effects of natural, spontaneous, or deliberate invention usually became "property" of the community in which they originated. Passing on these experiences and cultivating the accompanying knowledge to the next generations has become something obvious, one could say - natural. Today, however, this transmission of knowledge and skills is often interrupted by the appropriation of land and what it produces: both, becoming private goods, are subjected to extremely stressful use, to the detriment of people and the environment. The purpose of the analysis undertaken here is to outline the risks and effects of depriving individuals and communities of the right to dispose of resources and spontaneously acquired knowledge. The problem is not limited to a specific place or country, and awareness of the effects should be of interest to theoreticians and practitioners, especially those holding decision-making functions.